2016
DOI: 10.2169/internalmedicine.55.5190
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and Anemia with Anti-c-Mpl antibodies Effectively Treated with Cyclosporine in a Patient with Rheumatoid Arthritis and Chronic Renal Failure

Abstract: A 61-year-old woman with rheumatoid arthritis who was undergoing hemodialysis for end-stage renal failure was transferred to our hospital due to severe thrombocytopenia and anemia. A bone marrow biopsy showed the complete absence of megakaryocytes and erythroblasts. Cyclosporine treatment resulted in the improvement of her megakaryocyte and erythroblast levels, and a decrease in her serum level of anti-c-Mpl (thrombopoietin receptor) antibodies. After this initial improvement, her anemia progressively worsened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…AATP is a rare disease, and only 64 cases have been reported in the past 2 decades 1 , 5 , 6 , 12 - 16 , 21 - 23 . In the present case, bone marrow examination should have performed when we made a tentative diagnosis of ITP because thrombocytopenic conditions include ITP, AATP, and other thrombocytopenic disorders.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…AATP is a rare disease, and only 64 cases have been reported in the past 2 decades 1 , 5 , 6 , 12 - 16 , 21 - 23 . In the present case, bone marrow examination should have performed when we made a tentative diagnosis of ITP because thrombocytopenic conditions include ITP, AATP, and other thrombocytopenic disorders.…”
Section: Discussionmentioning
confidence: 72%
“…An autoimmune mechanism has been considered as the cause of AATP such as an antibody directed against TPO 1 or c-Mpl, 21 , 22 , 24 or cytotoxic immune cells against megakaryocyte precursors or progenitors 23 , 25 , 26 . In support of an autoimmune mechanism, associations with other autoimmune diseases, such as systemic lupus erythematosus, 21 , 24 , 25 rheumatoid arthritis, 12 Sjögren’s syndrome, 18 and adult-onset Still’s disease, 7 have been reported. As another cause, the involvement of estrogen has been suggested 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CsA can inhibit T lymphocytes through the following two pathways: i) CsA inhibits the generation of interleukin (IL)-2 ( 15 ); ii) CsA inhibits generation of the IL-2 receptor ( 16 ). CsA has been widely used in the treatment of various diseases, including aplastic anemia ( 17 ), nephritic syndrome ( 18 ), rheumatoid arthritis ( 19 ) and psoriasis ( 20 ). Studies have shown that CsA inhibits cyclophilin-D (Cyp-D), and then prevents the formation of mPTP ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can either occur isolated or be associated with systemic lupus erythematodus (SLE) (Cela et al, 2010;Ernestho-ghoud et al, 2015) and other autoimmune diseases (Hashimoto et al, 2016), as well as hematological malignancies such as non-Hodgkin lymphoma (Lugassy, 1996).…”
Section: Introductionmentioning
confidence: 99%